EMPLOYEE PERFORMANCE ANALYSIS WITH MOTIVATION AS AN INTERVENING VARIABLE AT PT BRANTA INDO NIAGA. - Werdimansyah, Farah; Hidayat, Rachmad; Rahayu, Sri; Fitrianty, Rifda (Smart Education, 2025)
Abstract: PT. Branta Indo Niaga's output level, the company's sales and production have fallen over the last four years. This study aims to ascertain how transformational leadership affects PT. Branta Indo Niaga employees' motivation. to determine how PT. Branta Indo Niaga employees' performance is affected by transformational leadership. to determine how motivation affects PT. Branta Indo Niaga's performance. to ascertain how transformational leadership affects worker performance using PT. Branta Indo Niaga's motivation as an intervening variable. To confirm the association between variables, this study used quantitative analysis and variation-based or component-based structural equation modeling (SEM), specifically partial least squares, or PLS. All 39 employees of PT. Branta Indo Niaga comprise the population used in this study. The sampling strategy is a saturated sample, meaning that all 39 employees of PT. Branta Indo Niaga are included. The study's findings demonstrate that PT. Branta Indo Niaga employees' motivation is significantly improved by transformational leadership. Employee performance at PT. Branta Indo Niaga is significantly improved by transformational leadership. Employee performance at PT. Branta Indo Niaga is significantly improved by motivation. The impact of transformative leadership on PT. Branta Indo Niaga employees' performance might be mitigated by motivation. Keyword: Human Resources, Transformational Leadership, Motivation, Employee Performance. Abstrak: Tingkat output PT. Branta Indo Niaga, penjualan dan produksi perusahaan telah turun selama empat tahun terakhir. Penelitian ini bertujuan untuk memastikan bagaimana kepemimpinan transformasional mempengaruhi motivasi karyawan PT. Branta Indo Niaga. untuk menentukan bagaimana kinerja karyawan PT. Branta Indo Niaga dipengaruhi oleh kepemimpinan transformasional. untuk menentukan bagaimana motivasi mempengaruhi kinerja PT. Branta Indo Niaga. untuk memastikan bagaimana kepemimpinan transformasional mempengaruhi kinerja pekerja dengan menggunakan motivasi PT. Branta Indo Niaga sebagai variabel intervening. Untuk mengkonfirmasi hubungan antara variabel, penelitian ini menggunakan analisis kuantitatif dan pemodelan persamaan struktural (SEM) berbasis variasi atau berbasis komponen, khususnya kuadrat terkecil parsial, atau PLS. Semua 39 karyawan PT. Branta Indo Niaga merupakan populasi yang digunakan dalam penelitian ini. Strategi pengambilan sampel adalah sampel jenuh, yang berarti bahwa semua 39 karyawan PT. Branta Indo Niaga disertakan. Temuan penelitian menunjukkan bahwa motivasi karyawan PT. Branta Indo Niaga ditingkatkan secara signifikan oleh kepemimpinan transformasional. Kinerja karyawan di PT. Branta Indo Niaga ditingkatkan secara signifikan oleh kepemimpinan transformasional. Kinerja karyawan di PT. Branta Indo Niaga ditingkatkan secara signifikan oleh motivasi. Dampak kepemimpinan transformatif terhadap kinerja karyawan PT. Branta Indo Niaga dapat dikurangi oleh motivasi. Kata kunci: Sumber Daya Manusia, Kepemimpinan Transformasional, Motivasi, Kinerja Karyawan.